Magnetic resonance evaluation of adnexal masses - Guerra, A. (2016)
Background: Accurate evaluation of adnexal masses allows correct surgical procedure, avoiding unnecessary surgery. Purpose: To evaluate the accuracy of magnetic resonance imaging (MRI) in the diagnosis of malignancy of adnexal lesions. Material and Methods: We retrospectively reviewed the pelvic MRI scans of 161 patients with 199 surgically confirmed adnexal masses, between November 1998 and June 2005. The criteria for adnexal malignancy were contrast-enhanced solid lesions, contrastenhanced solid components in mixed lesions (except those with low-signal-intensity solid components on T2-weighted imaging [T2WI]), contrast-enhanced papillary projections in cystic lesions (except those with low-signal-intensity papillary projections on T2WI), or septal thickness ]3 mm. Ascites, peritoneal metastasis, and pelvic adenopathy were also regarded as criteria for malignancy. Results: On MRI evaluation, 97 adnexal lesions were malignant and 102 were nonmalignant. Thirty-two percent of patients with ascites had benign lesions. Histopathologic evaluation of the adnexal lesions showed that 83 were malignant (true positives), 100 were non-malignant (true negatives), and seven were uncertain malignant potential tumors; two were false negative and seven were false positive. The MRI sensitivity and specificity for malignancy were 98% and 93%, respectively. MRI reached an accuracy of 95%, with a positive predictive value of 0.92 and a negative predictive value of 0.98 for malignant adnexal lesions. The kappa coefficient was 0.906, indicating almost perfect agreement between MRI and histological results. Conclusion: MRI is an accurate method for evaluating the malignancy of adnexal lesions.